(untitled) (Stylos, 2019)
This paper will to make a contribution for the analysis in dream and astrological justification given by the writers of the third century of the Christian era, mainly Herodian and Dion Cassius, on the nature of political power that the first emperor of the dynasty severe, Lucius Septimius Severus, obtained through dreams and omens that the emperor claimed to have had. To do this, try to size the fact that these astrological influences and dream have been in men, such as Severe, appear to influence participants have felt that since time immemorial have been blinded and influenced by man.